Antimicrobial activity of 1, 3, 4-thiadiazole derivatives: a recent review - Alam, Faruk (Journal of Applied Pharmaceutical Research, 2018)
A few five members’ aromatic systems having three hetero-atoms at symmetrical positions, for example, thiadiazoles have been considered broadly attributable to their intriguing pharmacological properties. These thiadiazole derivatives are the heterocyclic compound which contains the five member ring along with nitrogen and sulfur atoms. This recent study covers the most dynamic thiadiazole subordinates that have demonstrated significant biological activities, for example, anti microbial, anti inflammatory, anti tubercular, ant-diabetic, diuretics, anti depressant, radio-protective, anti-leishmanial and cytotoxic activity. This review likewise examines the structure-activity relationship (SAR) of the most powerful compounds. It can go about as an imperative tool for restorative scientists to create more current compounds having thiadiazole moiety that could be better operators regarding viability and safety.